The deindustrialisation/tertiarisation hypothesis reconsidered: a subsystem application to the OECD7 - Sandro Montresor; Giuseppe Vittucci Marzetti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
The diffusion of outsourcing, both national and international, and vertical FDIs among manufacturing firms, along with the higher integra- tion of business services in manufacturing, has recently led to question the empirical evidence supporting the Deindustrialisation/Tertiarisation (DT) hypothesis. Rather than a eal" phenomenon, it has been argued, DT would be an " one, mainly due to the reorganization of production across national and sectoral boundaries. The empirical studies that have dealt with the topic so far have not been able to effectively rule out such possibility, because of two main limitations: the sectoral level of the analysis and/or the national focus. In order to overcome them, the paper carries out an appreciative investigation of the actual extent of the DT occurred in the OECD area over the '80s and the '90s by moving from a sector to a subsystem perspective, thus retaining both direct and indirect relations, and by referring to a -World" of 7 OECD countries, thus taking into account the " dimension of the phenomenon. The results strongly support the DT hypothesis: although the weight of business sector services in the manufacturing subsystem increased, acting as a counterbalancing tendency to the manufacturing decline, subsystem shares significantly decreased, thus confirming DT as a more fundamental trend of modern economies.
Keywords: 330